2009
DOI: 10.1016/j.ophtha.2008.12.065
|View full text |Cite
|
Sign up to set email alerts
|

For Which Glaucoma Suspects Is It Appropriate to Initiate Treatment?

Abstract: Objective Because uncertainty exists about which glaucoma suspects should be treated, we sought to identify glaucoma suspects whom an expert panel could agree would be appropriate or inappropriate to treat. Design RAND/UCLA appropriateness method, a well-established procedure to synthesize the scientific literature with expert opinion to resolve uncertainty on a health topic. Participants Eleven-member panel composed of recognized international leaders in the field of glaucoma. Methods Based on a systema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Although glaucoma suspects often develop glaucoma, there is a lack of uniformity regarding when to initiate treatment in these patients. 2 , 7 The OHTS and additional studies found a variety of risk factors for the development of POAG that should be considered when determining how to manage glaucoma suspect patients, including older age, African American race, Hispanic ethnicity, male sex, larger cup-to-disc ratios (CDR), high IOP, family history of glaucoma, higher visual field standard deviation, greater pattern standard deviation (PSD), type 2 diabetes, high myopia, and a thinner central corneal measurement. 4 , 5 , 8 12 The American Academy of Ophthalmology's Preferred Practice Pattern on management of glaucoma suspect patients recommends determining if a patient is at high risk for developing glaucomatous optic neuropathy while considering the potential benefits and risks of treatment.…”
Section: Introductionmentioning
confidence: 99%
“…Although glaucoma suspects often develop glaucoma, there is a lack of uniformity regarding when to initiate treatment in these patients. 2 , 7 The OHTS and additional studies found a variety of risk factors for the development of POAG that should be considered when determining how to manage glaucoma suspect patients, including older age, African American race, Hispanic ethnicity, male sex, larger cup-to-disc ratios (CDR), high IOP, family history of glaucoma, higher visual field standard deviation, greater pattern standard deviation (PSD), type 2 diabetes, high myopia, and a thinner central corneal measurement. 4 , 5 , 8 12 The American Academy of Ophthalmology's Preferred Practice Pattern on management of glaucoma suspect patients recommends determining if a patient is at high risk for developing glaucomatous optic neuropathy while considering the potential benefits and risks of treatment.…”
Section: Introductionmentioning
confidence: 99%